A functional equation characterizing cubic polynomials and its stability. (23rd October 2001) - Jung, Soon-Mo; Sahoo, Prasanna K.
Abstract : We study the generalized Hyers-Ulam stability of the functional equationf [ x 1, x 2, x 3 ] = h ( x 1 + x 2 + x 3 ) .